2014
DOI: 10.1017/s0007114514001615
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous associations of insoluble dietary fibre intake with subsequent glycosylated Hb levels among Chinese adults with type 2 diabetes: a quantile regression approach

Abstract: Dietary fibre intake has been suggested to reduce blood glucose levels in diabetic patients, particularly when glycosylated Hb (HbA 1c ) levels are high. In the present study, we used a quantile regression (QR) approach to characterise the possible heterogeneous associations of dietary fibre intake with HbA 1c levels in Chinese diabetic patients. A total of 497 diabetic patients participated in the baseline survey in 2006 and in the follow-up survey in 2011, both of which were conducted in Pudong New Area of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Isken et al [11] reported that supplementing the diet with insoluble cereal fiber resulted in significantly lower weight gain and improved insulin sensitivity. Tan et al [12] also found the associations of IDF intake and glycemic index value with subsequent HbA1c levels. In spite of these efforts, whether and how IDF affects the gut microbiota, key lipometabolism, and satiety hormone secretion is largely unknown.…”
Section: Introductionmentioning
confidence: 91%
“…Isken et al [11] reported that supplementing the diet with insoluble cereal fiber resulted in significantly lower weight gain and improved insulin sensitivity. Tan et al [12] also found the associations of IDF intake and glycemic index value with subsequent HbA1c levels. In spite of these efforts, whether and how IDF affects the gut microbiota, key lipometabolism, and satiety hormone secretion is largely unknown.…”
Section: Introductionmentioning
confidence: 91%
“…no assumptions are made about a relationship being either linear or curvilinear in any pre-specified form; meanwhile, intercepts and slopes are not assumed constant from one quantile to another. Interestingly, the observations from Tan et al ( 1 ) indicate a possible broadly inverted U-shaped relationship for the size of associations for the decrease in HbA 1c concentrations with higher insoluble fibre intake (their Fig. 1) and a possible broad U-shaped association between the increase in HbA 1c concentrations and higher GI in the upper quantiles (their Fig.…”
mentioning
confidence: 91%
“…For many a reader, clarity is likely to appear weaker still because QR is currently not a familiar statistical procedure. Hence, considering these weaknesses together, Tan et al ’s study ( 1 ) inevitably informs us about the uncertain strengths of the association (probably underestimates) between the change in HbA 1c concentrations over 5 years and insoluble dietary fibre and GI intakes at each possible quantile of HbA 1c (their ( 1 ) Table 2 and Figs. 1 and 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations